2018
DOI: 10.1016/j.coviro.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Genome packaging in multi-segmented dsRNA viruses: distinct mechanisms with similar outcomes

Abstract: Segmented double-stranded (ds)RNA viruses share remarkable similarities in their replication strategy and capsid structure. During virus replication, positive-sense single-stranded (+)RNAs are packaged into procapsids, where they serve as templates for dsRNA synthesis, forming progeny particles containing a complete equimolar set of genome segments. How the +RNAs are recognized and stoichiometrically packaged remains uncertain. While bacteriophages of the Cystoviridae family rely on specific RNA-protein intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
69
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 69 publications
1
69
0
Order By: Relevance
“…The Cystoviridae are a family of bacterial dsRNA viruses and although they are somewhat smaller and simpler than the Reoviridae (they possess only three genome segments) it has been proposed that they share a common ancestor 19 . The Cystoviridae have acted as a model system for understanding assembly and RNA packaging in dsRNA viruses 20 22 and the first stage in the assembly of these viruses is the formation of a highly indented SLP 23 . There is a striking similarity between the indented SLPs of phage Phi8 (representative of the Cystoviridae ) and reovirus (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The Cystoviridae are a family of bacterial dsRNA viruses and although they are somewhat smaller and simpler than the Reoviridae (they possess only three genome segments) it has been proposed that they share a common ancestor 19 . The Cystoviridae have acted as a model system for understanding assembly and RNA packaging in dsRNA viruses 20 22 and the first stage in the assembly of these viruses is the formation of a highly indented SLP 23 . There is a striking similarity between the indented SLPs of phage Phi8 (representative of the Cystoviridae ) and reovirus (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Considering this, it could be expected that packaging of segmented viral genomes is a highly selective process. The existence of a selective packaging mechanism has already been demonstrated for segmented RNA viruses of other families such as influenza virus and rotavirus [13][14][15] . Reverse genetics and electron microscopy studies on influenza virus showed that the eight genome segments use packaging signals to assemble into a supramolecular complex with a '7+1' configuration [16][17][18][19] .…”
Section: Introductionmentioning
confidence: 94%
“…We generally use the human RV for TEM study, in which viroplasm is relatively rare. The critical concentration of NSP2 outside of viroplasm is far too low for DLPs assembly (Borodavka et al 2017(Borodavka et al , 2018. It has been shown that primary human RV clinical isolates grow very well in secondary monkey kidney cells, far better than in MA104 African green monkey kidney cells (Ward et al 1984).…”
Section: Tep Formationmentioning
confidence: 99%